1996
DOI: 10.1038/380526a0
|View full text |Cite
|
Sign up to set email alerts
|

Activation of the primary visual cortex by Braille reading in blind subjects

Abstract: Primary visual cortex receives visual input from the eyes through the lateral geniculate nuclei, but is not known to receive input from other sensory modalities. Its level of activity, both at rest and during auditory or tactile tasks, is higher in blind subjects than in normal controls, suggesting that it can subserve nonvisual functions; however, a direct effect of non-visual tasks on activation has not been demonstrated. To determine whether the visual cortex receives input from the somatosensory system we … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

43
651
8
11

Year Published

1997
1997
2013
2013

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 1,065 publications
(713 citation statements)
references
References 17 publications
43
651
8
11
Order By: Relevance
“…For example, Neville et al reported changes in evoked visual response in congenitally deaf persons and interprfeted it as a neuroplastic change, in which visual input invades unused areas of the auditory cortex. [27] These fi nding were later confi rmed in studies of subjects with single sensory deprivation (auditory or visual) using neuroimaging techniques with greater spatial resolution (fMRI and PET), [5,[28][29][30] which demonstrated extensive cerebral reorganization in cortical areas, showing how auditory areas of the brain are activated by visual stimuli in deaf persons, [3] while the visual cortex is activated by somatosensory and auditory stimuli in blind persons. [5,28,31,32] Our fi ndings could be ascribed to this form of neuroplasticity, CMP.…”
Section: Discussionmentioning
confidence: 83%
See 1 more Smart Citation
“…For example, Neville et al reported changes in evoked visual response in congenitally deaf persons and interprfeted it as a neuroplastic change, in which visual input invades unused areas of the auditory cortex. [27] These fi nding were later confi rmed in studies of subjects with single sensory deprivation (auditory or visual) using neuroimaging techniques with greater spatial resolution (fMRI and PET), [5,[28][29][30] which demonstrated extensive cerebral reorganization in cortical areas, showing how auditory areas of the brain are activated by visual stimuli in deaf persons, [3] while the visual cortex is activated by somatosensory and auditory stimuli in blind persons. [5,28,31,32] Our fi ndings could be ascribed to this form of neuroplasticity, CMP.…”
Section: Discussionmentioning
confidence: 83%
“…[2][3][4] Furthermore, it has been shown that in the congenitally blind, visual cortical areas are activated during linguistic processing via touch. [5] This evidence of cortical reorganization is known as cross-modal plasticity (CMP).…”
Section: Introductionmentioning
confidence: 99%
“…There is growing evidence for early sensory interactions between vision and touch, and it has been suggested that the reorganization of the visual cortex of blind individuals that occurs in the absence of visual input reinforces preexisting connections between the somatosensory and visual cortices (see a review by Pascual-Leone, Amedi, & Fregni, 2005). Consistent with this suggestion, studies have demonstrated that the visual cortex of blind individuals is activated during tasks such as Braille reading (Cohen et al, 1997;Sadato et al, 1996) and haptic object recognition (Amedi, Raz, Azulay, Malach, & Zohary, 2010). Moreover, the existence of networks between vision and touch in normally sighted individuals is supported by neuroimaging studies; visual areas have been shown to be activated during tactile orientation discrimination (Sathian & Zangaladze, 2002;Sathian, Zangaladze, Epstein, & Grafton, 1999), haptic object recognition (Amedi, Jacobson, Hendler, Malach, & Zohary, 2002;Amedi et al, 2010;Deibert, Kraut, Kremen, & Hart, 1999;James, Humphrey, Gati, Servos, Menon, & Goodale, 2002;Pietrini et al, 2004), and Braille reading in sighted subjects following 5 days of complete visual deprivation (Merabet et al, 2008).…”
Section: Introductionmentioning
confidence: 93%
“…Sadato et al [1996] used positron emission tomography (PET) to demonstrate that Braille reading in these subjects activated the somatosensory cortex assigned to the Braille reading fingers, as well as the primary visual cortex. They also showed that transient inactivation of the occipital cortex with transcranial magnetic stimulation (TMS) impaired tactile discrimination in the blind subjects but did not affect sensation in nonblind individuals [Cohen et al, 1997].…”
Section: Clinical Examples Of Plasticity and Reorganization In Cerebrmentioning
confidence: 99%